2016
DOI: 10.1136/jnnp-2015-312723
|View full text |Cite
|
Sign up to set email alerts
|

Defining and validating a short form Montreal Cognitive Assessment (s-MoCA) for use in neurodegenerative disease

Abstract: Introduction Screening for cognitive deficits is essential in neurodegenerative disease. Screening tests, such as the Montreal Cognitive Assessment (MoCA), are easily administered, correlate with neuropsychological performance and demonstrate diagnostic utility. Yet, administration time is too long for many clinical settings. Methods Item response theory and computerised adaptive testing simulation were employed to establish an abbreviated MoCA in 1850 well-characterised community-dwelling individuals with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 47 publications
4
65
2
2
Order By: Relevance
“…In accordance with Roalf et al 1's study, full MoCA demonstrated a relatively high value to discriminate healthy controls from patients with aMCI (area under the curve (AUC) value=0.814, p<0.001, 95% CI (0.749 to 0.878)). The diagnostic accuracy of MoCA was 0.805 (p<0.001, 95% CI (0.728 to 0.882)) for aMCI-sd and 0.947 for aMCI-md (p<0.001, 95% CI (0.911 to 0.982)).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with Roalf et al 1's study, full MoCA demonstrated a relatively high value to discriminate healthy controls from patients with aMCI (area under the curve (AUC) value=0.814, p<0.001, 95% CI (0.749 to 0.878)). The diagnostic accuracy of MoCA was 0.805 (p<0.001, 95% CI (0.728 to 0.882)) for aMCI-sd and 0.947 for aMCI-md (p<0.001, 95% CI (0.911 to 0.982)).…”
supporting
confidence: 86%
“…We read with great interest of the study defining and validating the screening accuracy of short form Montreal Cognitive Assessment (s-MoCA) in individuals with different cognitive status 1. This 5-min s-MoCA is attractive because it achieves the goal for adequate screening of cognitive impairment in an ageing population.…”
mentioning
confidence: 99%
“…We acknowledge that this can be a significant burden on the clinician. Thus, we recently published a valid brief version of the MoCA, called the s-MoCA [25]. This brief version is 8 questions long and takes approximately 5 minutes to administer.…”
Section: Methodsmentioning
confidence: 99%
“…The disadvantage is that they are complex, require some training and are usually performed using special software programs. Over the last several years, several preexisting neurologic rating scales have been evaluated and revised using LTT models [72][73][74][75].…”
Section: Measurement Theories: Classical Test Theory and Latent Traitmentioning
confidence: 99%